Acute Skin Wounds Treated with Mesenchymal Stem Cells and Biopolymer Compositions Alone and in Combination: Evaluation of Agent Efficacy and Analysis of Healing Mechanisms - Ekaterina Silina; Victor Stupin; Natalia Manturova; Vitaly Vasin; Konstantin Koreyba; Petr Litvitskiy; Alexander Saltykov; Zalim Balkizov (MDPI AG, 2021)
We studied the efficacy of using mesenchymal stem cells (MSC) and a polymeric compound (based on chitosan and cellulose with integrated cerium dioxide nanoparticles (PCCD)) in wound healing, and to compare the effects with various invasive and external drugs used for the same purpose. Two wounds were made on the backs of each of 112 Wistar rats, removing the skin. Eight groups were studied: Control_0-intact wounds; Control_ss-0.9% NaCl injections; MSC injections; Control_msc-intact wounds on the opposite side of the body from the MSC group; external application of the PCCD; external application of a combination of the drugs PCCD + MSC; DCh -ointment Dioxomethyltetrahydropyrimidine + Chloramphenicol; and DHCB-injections of a deproteinized hemoderivative of calf blood. After 14 days, we evaluated the state and size of the wounds, studied the level of microcirculation, performed a histological study, and identified and counted the different types of cells. The most effective remedy was combination PCCD + MSC. The treatments in the PCCD and MSC groups were more effective than in the DHCB and DCh groups. Invasive drugs and DCh slowed the regeneration process. DHCB did not affect the rate of healing for acute wounds without ischemia during the first week. The proven efficacy of developed polymeric compounds demonstrates the feasibility of further studies in clinical practice.